The Interactions Price Synchronicity: Connections between Indonesia's Stock Index and Asian Equities Markets - Mubarok, Faizul; Wibowo, Martino; Arifin, Andi Harmoko; Prasetiyo, Yudhi; Aumeboonsuke, Vesarach (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Introduction / Main Objectives: This research aims to investigate how other Asian stock markets have affected the Indonesian market and how much of an effect they have had. Background Problems: Looking at the capital market is a way to measure the health and growth of a country's economy. Consequently, a nation will employ a wide range of measures to lessen the impact of potential threats and make the most of its available resources. Research Methods: Using daily time series data from 2010 to 2022, the number of observations in this study reached 2712. This study employs vector autoregression (VAR). Findings/Results: The study's findings indicated that the stock indices of Malaysia and Thailand affected the Indonesian indices. The Indonesian stock market index (IHSG) reacted negatively to the indices of the Philippines (PSEI), Malaysia (KLCI), and South Korea (KOSPI) and positively to those of Hong Kong (HANG SENG), Thailand (SETI), and Japan (NIKKEI). Conclusion: Capital market portfolio diversification allows investors to evaluate alternative investing techniques. It is essential to have a diversified worldwide portfolio while trading on Asian exchanges. The study's findings shed light on the Asian stock market's tendencies and patterns in novel ways.